Performance and responsiveness to change of PROMIS UE in patients undergoing total shoulder arthroplasty. Issue 10 (20th January 2022) - Pines, Yaniv; Gordon, Dan; Alben, Matthew; Kwon, Young W.; Zuckerman, Joseph D.; Virk, Mandeep S.
Abstract: The Patient‐Reported Outcomes Measurement Information System Upper Extremity Computer Adaptive Test (PROMIS UE CAT) is a newer patient‐reported outcome measure for upper extremity physical function. To date, no longitudinal study exists assessing PROMIS UE CAT responsiveness in patients undergoing shoulder arthroplasty. The purpose of this prospective longitudinal study is to report PROMIS UE CAT responsiveness to change and correlation to legacy instruments in patients undergoing total shoulder arthroplasty (TSA). Ninety‐six patients (97 shoulders) undergoing TSA completed the PROMIS UE, Oxford Shoulder Score (OSS), American Shoulder and Elbow Surgeons (ASES), and Simple Shoulder Test (SST) preoperatively and postoperatively at 6 weeks, 12 weeks, and after 6 months. Spearman's correlation coefficients ( r ) were calculated between PROMIS UE and other scores at each time‐point. Responsiveness to change was assessed using the effect size (Cohen's  d ) and standardized response mean compared with the preoperative time‐point. Floor and ceiling effects were also assessed. PROMIS UE CAT demonstrated positive responsiveness at all time‐points after TSA. It demonstrated excellent correlation (range: 0.68–0.84) with ASES, SST, and OSS at all postoperative time‐points, but the correlation was weaker ( r  < 0.6, except OSS) preoperatively. Only OSS and SST showed ceiling effects at the 6–12‐month time‐point (16.8% and 18.2%, respectively). PROMIS UE CAT responsiveness to change and strength of correlation with legacy instruments improves with time elapsed after TSA. Further quantification of meaningful responsiveness to change will require estimation of the minimal clinically important difference and substantial clinical benefit for PROMIS UE CAT.